Playful Mobility Choices: Motivating informed mobility decision making by applying game mechanics - A. Millonig; K. Mitgutsch (EAI Endorsed Transactions on Ambient Systems, 2014)
Motivating people to change their mobility behaviour patterns towards more sustainable forms of mobility is one of the major challenges regarding climate change and quality of life. Recently, an increasing amount of attempts to use gamification for triggering such behavioural changes can be observed. However, little is known about the actual impact of using game elements. This contribution describes a concept for systematically analysing the group-specific effects of different game mechanics on mobility decision processes (e.g. mode and route choice). Based on theoretical findings concerning player types and mobility styles we developed a framework for identifying effective game mechanics motivating users to explore mobility alternatives and take more informed and more sustainable mode or route choice decisions. The results will form the basis for implementing game mechanics in mobility information services motivating users to explore unfamiliar but more sustainable mobility options.